Cardiorespiratory Fitness as a Mediator of the Influence of Diet on Obesity in Children - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The association between diet and obesity has been widely studied and it continues to be controversial; however, the extent to which cardiorespiratory fitness (CRF) acts as a confounder or mediator in this relation has not been analyzed. The aim of this study is to examine if the relation between diet and obesity is mediated by CRF. In this cross-sectional study, fat mass (by electronic bioimpedance) was measured in 320 schoolchildren, aged 9–11 years. Diet was measured through two computerised 24-h dietary recalls and CRF was assessed by the 20-m shuttle run test. Simple mediation analyses were fitted. CRF acts as a partial mediator in the negative relationship between dietary factors (energy intake/weight, carbohydrate intake/weight, protein intake/weight, and fat intake/weight) and fat mass. The percentage of mediation ranged from 24.3 to 33.2%. Thus, Spanish schoolchildren with higher levels of energy and macronutrients intake had lower adiposity levels, especially when they had good levels of CRF. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.